Biomechanics for inclusive urban design: effects of tactile paving on older adults' gait when crossing the street - Faruk, Mohammad; Thies, S.B.; Kenney, L.P.J.; Howard, D.; Nester, C.; Ormerod,M.; Newton, R.; Baker, R.; MacLennan, H. (© 2011 Published by Elsevier Inc., 2016)
This article was published in the Journal of Biomechanics [©2011 Published by Elsevier Inc.] and the definite version is available at: http://dx.doi.org/10.1016/j.jbiomech.2010.12.016 The article website is at: http://www.sciencedirect.com/science/article/pii/S0021929011000157